Patterns in renal diseases diagnosed by kidney biopsy: A single-center experience - Taehoon Yim; Sang-Un Kim; Sangmi Park; Jeong-Hoon Lim; Hee-Yeon Jung; Jang-Hee Cho; Chan-Duck Kim; Yong-Lim Kim; Man-Hoon Han; Yong-Jin Kim; Ji-Young Choi; Sun-Hee Park (The Korean Society of Nephrology, 2020)
Background : : The worldwide incidence of renal disease diagnosed by a kidney biopsy varies with age, race, sex, and region. Owing to a lack of studies and limited research resources for this disease in Korea, we investigated renal disease patterns by analyzing data from kidney biopsies performed over 13 years in a university-based teaching hospital in Korea. Methods : : Among 2,053 kidney biopsies performed from 2001 to 2013 at Kyungpook National University Hospital, 1,924 were retrospectively analyzed for histopathologic, demographic, and clinical data as well as laboratory results. Results : : Among the 1,924 studied kidney biopsies, 1,078 were males (56.0%) and the mean age was 37.7 ± 16.5 years. Asymptomatic urinary abnormalities were the most common clinical manifestation (62.5%). Immunoglobulin A nephropathy (IgAN) was the most common primary glomerular disease (37.4%), followed by minimal change disease (MCD), membranous nephropathy (MN), focal segmental glomerulonephritis and crescentic glomerulonephritis. Secondary glomerular diseases accounted for 10.3% of the total biopsies, with lupus nephritis being the most common (4.6%) followed by Henoch-Schönlein purpura nephritis and diabetic nephropathy. The most common cause of nephrotic syndrome was MCD (42.1%) followed by MN. Among patients seropositive for hepatitis B or C, IgAN (28.3% and 21.4%, respectively) was the most common cause. Conclusion : : IgAN and lupus nephritis were the most common primary and secondary glomerular diseases, respectively. Race, region, and practice patterns may affect renal disease patterns in different cohorts.